STRATEGI KLASTER INDUSTRI MENGHADAPI PASAR GLOBAL - Andriyanto, Irsad; Nurjanah, Nurjanah (BISNIS, 2015)
ASEAN  Economic  Community  (AEC)  2015  can  bring  both  positive and  negative  impact  on  MSMEs.  To  deal  with  any  negative  impacts,SMEs  need  for  strategies  to  exist  and  continue  growing.  One  such strategy  is  the  cluster  approach.  This  approach  is  done  by  groupingthe  core  industries  that  are  interconnected,  both  supporting industries  (supporting  industries),  industries  related    (related industries), supporting    services,    economic    infrastructure,  research, training,     education,     information infrastructure,     technology infrastructure,  natural  resources,  and  any  related  institutions. Cluster  is  also  a  way  to  set  some  economic  development  activities.  Based  on  the  result, Strategies  to  Increase  Industry  Competitiveness  in Facing  ASEAN  Economic  Community  (AEC)  is  done  by:  1.  The  use of  core  competencies  in  seeking  to  improve  the  competitiveness clusters.  And  2.  Creating  their  competitive  advantage  cluster  based on RBV (Resources Based Value) approach.